1989
DOI: 10.1192/bjp.155.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Eating Attitudes in Young Insulin-Dependent Diabetics

Abstract: All insulin-dependent diabetics between the ages of 16 and 25 years attending the diabetic clinic at the Royal Infirmary, Edinburgh, (152 women and 139 men) were asked to complete the EAT, the EDI, and the GHQ, and to provide a control subject (sibling or close friend) of similar age who would do likewise. Marked differences were found between diabetic women (but not men) and their controls in eating attitudes, in many of the psychological characteristics associated with eating disorders, and in GHQ scores. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
1
3

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 22 publications
5
54
1
3
Order By: Relevance
“…10,22,42, 63 We 10 found that screening for disordered behavior using the modified Diagnostic Survey for Eating Disorders, 22,64 independent of an eating disorder diagnosis, allowed demonstration of a clear association between disordered behavior, impaired metabolic control, and an increased risk of microvascular complications.…”
Section: Screening For Disordered Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…10,22,42, 63 We 10 found that screening for disordered behavior using the modified Diagnostic Survey for Eating Disorders, 22,64 independent of an eating disorder diagnosis, allowed demonstration of a clear association between disordered behavior, impaired metabolic control, and an increased risk of microvascular complications.…”
Section: Screening For Disordered Behaviormentioning
confidence: 99%
“…46,67 We and others have consistently shown that eating disturbances in association with diabetes lead to significant impairments in metabolic control. 7,8,10,22,23,26,27,32,42,54,63,68 In an early review of 57 case reports in which diabetes and an eating disorder were documented, Marcus and Wing 69 reported that more than 75% evidenced poor metabolic control.…”
Section: Impaired Metabolic Controlmentioning
confidence: 99%
“…Although it is unclear whether eating disorders are more prevalent among patients with type 1 diabetes, eating disorders per se do seem to be associated with poorer glycemic control and increased risk for complications (4,7,8,10,14). For example, Rydall et al (15) reported that 86% of young women who displayed high levels of disordered eating developed retinopathy after 5 years compared with only 24% of women with normal eating patterns.…”
mentioning
confidence: 99%
“…Adolescence is a developmental period in which body image is of particular concern, and the increased prevalence of eating disorders in females during this developmental period has been well documented (7,18,19). The available literature suggests that body size (including weight gain), body image (including body dissatisfaction), adolescent age, and female sex are all predictive of disordered eating attitudes and behaviors in both healthy subjects and those with diabetes (2,3,7,11,19).…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Parte da literatura parece inconclusiva quanto à verificação da prevalência da comorbidade. Alguns estudos controlados com mulheres jovens diabéticas do tipo 1 não encontraram qualquer diferença de prevalência de transtornos alimentares entre portadoras ou não de DM.…”
Section: Introductionunclassified